PENERAPAN BERKELANJUTAN MELALUI PEMANFAATAN BENANG SISA MENJADI PRODUK RAJUTAN DEKORASI INTERIOR - Fivanda, Fivanda; Hung, Jennifer; Vanesa, Vanesa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
Digitization and technology mobilization have evolved rapidly. Generation Z and post-generation Z play a key role in the transformation of education and interaction with technology. Generation Z is a generation that is already familiar with technology and has an average birth year of 1997-2012. Meanwhile, post generation Z is the generation born in 2013 and above until now. Generation Z and post generation Z are characterized by fast learning through digital platforms. In the midst of technological change and the Internet of Things (IoT), it is very important to ensure that the digital generation can utilize social potential and contribute to sustainable concepts. The concept of sustainability is important to introduce to generation Z. The use of leftover yarn waste is a conservation and reuse of resources as well as a form of concern for the environment. By continuing cooperation in PKM activities with partner Yayasan Rumah Pagi Bahagia Bintaro through training in the utilization of leftover knitting yarn. The target of partner participants aged 11-16 years who are included in the generation Z classification. In the training activities, the utilization of leftover knitting yarn into interior decoration aims to produce valuable products and produce interior decoration products such as coasters, tablecloths and wall hangings with various knitting techniques. The method of activity is offline by providing training to 20 participants aged 11-16 years from the fostered children of PKM partners. This training is also prepared with a video guide to the steps of knitting leftover yarn. The result of the PKM activity is the use of leftover yarn waste from knitting from previous activities into interior decoration products that are not only of creative value but generation Z can better understand the concept of sustainability in everyday life ABSTRAK Digitalisasi dan mobilisasi teknologi telah berkembang pesat. Generasi Z dan post generasi Z memainkan peran kunci dalam transformasi pendidikan dan interaksi dengan teknologi. Generasi z merupakan generasi yang sudah mengenal teknologi dan rata-rata memiliki tahun kelahiran 1997-2012. Sedangkan post generasi Z merupakan generasi yang lahir di tahun 2013 keatas sampai dengan saat ini. Generasi Z dan post generasi Z berkarakteristik belajar cepat melalui platform digital. Di tengah perubahan teknologi dan Internet of Things (IoT) sangat penting untuk memastikan bahwa generasi digital dapat memanfaatkan potensi sosial dan berkontribusi terhadap konsep berkelanjutan. Konsep keberlanjutan ini penting untuk dikenalkan kepada generasi Z. Penggunaan limbah benang sisa rajut dari kegiatan PKM sebelumnya merupakan kegiatan konservasi dan penggunaan kembali sumber daya serta wujud kepedulian terhadap lingkungan. Dengan melanjutkan kerjasama dalam kegiatan PKM dengan mitra Yayasan Rumah Pagi Bahagia Bintaro melalui pelatihan pemanfaatan benang sisa merajut. Target dari peserta mitra dengan usia 11-16 tahun yang masuk dalam klasifikasi generasi Z. Dalam kegiatan pelatihan pemanfaatan benang sisa merajut menjadi dekorasi interior bertujuan untuk menghasilkan produk bernilai guna dan menghasilkan produk dekorasi interior seperti tatakan gelas, taplak meja dan hiasan dinding dengan berbagai teknik merajut. Metode kegiatan secara luring dengan pemberian pelatihan kepada 20 peserta berusia 11-16 tahun dari anak binaan mitra PKM. Pelatihan ini juga dipersiapkan dengan panduan video langkah-langkah merajut benang sisa. Hasil dari kegiatan PKM penggunaan limbah benang sisa merajut dari kegiatan sebelumnya menjadi produk dekorasi interior yang tidak hanya bernilai kreatif tetapi generasi Z dapat lebih memahami konsep berkelanjutan dalam kehidupan sehari-hari